Influence of relative humidity on heterogeneous kinetics of NO2 on kaolin and hematite1. Issue 29 (7th August 2015) - Liu, Yongchun; Han, Chong; Ma, Jinzhu; Bao, Xiaolei; He, Hong
<x xml:space="preserve">Abstract</x> In order to obtain reliable kinetic parameters, it is required to measure the reaction kinetics of important heterogeneous reactions at ambient relative humidity (RH).